The effect of coating condition and aqueous phase composition on the performance of thin film composite reverse osmosis flat sheet membranes - Kormin, Faridah (2005)
Thin film composite (TFC) layers are formed using interfacial polymerization reaction between an aqueous phase and organic phase on membrane supports. In the preparation of thin film composite membrane, there are many interfacial reaction factors that influence the membrane performance, amongst them are dipping time, curing temperature and composition of aqueous phase. Thus in this project these factors were studied in two stages. In the preliminary stage, the effect of dipping time and curing temperature on the performance of TFC membrane were evaluated using two different kinds of polymer membrane supports, cellulose acetate and polysulfone. Initial results revealed that dipping time does not affect the performance of TFC membranes especially rejection rate but curing temperature have significant influence. Curing temperature ranging from 40??C to 100??C was used during the interfacial reaction process. Cellulose acetate TFC membranes cured at 60??C exhibited highest rejection rate of 76% whilst polysulfone TFC membranes cured at 80??C showed not only highest rejection rate of 80% but also excellent flux rates. Since polysulfone TFC membranes showed superior performance compared to cellulose acetate, it is chosen for the second stage of the experiment. In this stage, a systematic experimental design based on the response surface methodology was used to identify the significant interfacial reaction factors which influence the membrane performance. The factors considered were the composition of aqueous phase that includes the ratio of m-phenyldiamine to hydroquinone as monomer, percent of tetrabutylammonium bromide as a catalyst and percent of sodium hydroxide as an acid acceptor. Rejection and flux rates were the response variables investigated. The experimental results indicate that the proposed mathematical model suggested could adequately describe the performance indicators within the limits of the factors that are being investigated.